Re: How to simplify certain covariance expressions using

*To*: mathgroup at smc.vnet.net*Subject*: [mg128039] Re: How to simplify certain covariance expressions using*From*: Bob Hanlon <hanlonr357 at gmail.com>*Date*: Mon, 10 Sep 2012 04:06:20 -0400 (EDT)*Delivered-to*: l-mathgroup@mail-archive0.wolfram.com*Delivered-to*: l-mathgroup@wolfram.com*Delivered-to*: mathgroup-newout@smc.vnet.net*Delivered-to*: mathgroup-newsend@smc.vnet.net*References*: <20120909213324.167C06765@smc.vnet.net>

You cannot run variable names together. Multiplication needs a space or an explicit * cov = (ea + ex) (ea + ey); Assuming[ex*ey == 0, Simplify[cov]] ea (ea + ex + ey) Simplify[cov, Assumptions -> ex*ey == 0] ea (ea + ex + ey) Or more compactly, Simplify[cov, ex*ey == 0] ea (ea + ex + ey) Or by replacement, (cov // Expand) /. ex*ey -> 0 ea^2 + ea*ex + ea*ey Bob Hanlon On Sun, Sep 9, 2012 at 5:33 PM, <hewei2004 at gmail.com> wrote: > Hi, > > I have a certain case of covariance to simplify. > > Suppose I have the following expression: > cov=(ea+ex)(ea+ey)=eaea+eaex+eaey+exey > > How can I assume that whenever ex times ey ,the product is 0, so that the expression I want to get out of is > > Assuming[exey=0,Refine[cov]]=eaea+eaex+eaey > So that the last term:exey, drops out. > > My problem is that the Assuming[] function won't take exey=0 as a valid assumption. Is there any way to do this using some other function or I typed something wrong? >

**References**:**How to simplify certain covariance expressions using***From:*hewei2004@gmail.com